Attitudes in an interpersonal context: Psychological safety as a route to attitude change - Itzchakov, Guy; DeMarree, Kenneth G. (Frontiers in Psychology, 2022)
Interpersonal contexts can be complex because they can involve two or more people who are interdependent, each of whom is pursuing both individual and shared goals. Interactions consist of individual and joint behaviors that evolve dynamically over time. Interactions are likely to affect people’s attitudes because the interpersonal context gives conversation partners a great deal of opportunity to intentionally or unintentionally influence each other. However, despite the importance of attitudes and attitude change in interpersonal interactions, this topic remains understudied. To shed light on the importance of this topic. We briefly review the features of interpersonal contexts and build a case that understanding people’s sense of psychological safety is key to understanding interpersonal influences on people’s attitudes. Specifically, feeling psychologically safe can make individuals more open-minded, increase reflective introspection, and decrease defensive processing. Psychological safety impacts how individuals think, make sense of their social world, and process attitude-relevant information. These processes can result in attitude change, even without any attempt at persuasion. We review the literature on interpersonal threats, receiving psychological safety, providing psychological safety, and interpersonal dynamics. We then detail the shortcomings of current approaches, highlight unanswered questions, and suggest avenues for future research that can contribute in developing this field.